ANALISIS PARTISIPASI DAN POLA KOMUNIKASI ANTARA MASYARAKAT DENGAN PEMERINTAH DALAM UPAYA MEMINIMALISASI KONFLIK PEMBANGUNAN - Suwignyo Rahman; Istiono Istiono; Lisa Mardiana; Wahid Abdulrahman (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2009)
In this reform era, the development in Indonesia start to walk with new paradigm that is positioning community as a development subject and government as a development facilitator. Community and a group of trade community will to compose effectively a model participation system, and government also will to compose effectively of model communication system to community in development so hopes will can minimalist development of conflict. This research taken case study of development policy in Relocation PKL Policy in Surakarta City and have been sitting with Land Exemption For Semarang – Solo’s Toll Road Policy in Semarang City with more focus on community’s participation and groups of trade community system analysis and communication from government to community with the comprehensive and connected. This research has done in June – November 2008 with location in Surakarta and Semarang City. This research used qualitative analysis as main unsure that is descriptive analysis. This research used primary’s data and secondary data resources. The respondent at this research decision used purposive sampling technique. Than collecting data shape in-depth interview, lecturer studies and documentation. For validity data in this research, researcher used descriptive qualitative analysis method. Interpretative data with integrated, with the triangulation also with analysis. The result of this research is participation and communication system at the relocation of PKL in Surakarta City has worked by Surakarta’ Government with the integrated concept and implementation technique and to connected well with PKL in Surakarta city’s participation system, that’s to front of organizing, empowerment, dialogue and negotiation so to create a good model of participation and communication system and to minimalist development conflict. Participation and communication system of Land Exemption For Semarang – Solo’s Toll Road in Semarang, in one side show successful in Land Exemption For Toll Road but in the other side not yet accommodation community aspiration and a group of trade community fully, by participative and to front of individual and group resolution so caused doesn’t finish better in individual and group that consistent to development Toll Road so development conflict is still go on and doesn’t finish well.